Fabrication of robust superhydrophobic surfaces via aerosol-assisted CVD and thermo-triggered healing of superhydrophobicity by recovery of roughness structures. Issue 29 (11th July 2019) - Guo, Xiao-Jing; Xue, Chao-Hua; Sathasivam, Sanjayan; Page, Kristopher; He, Guanjie; Guo, Jian; Promdet, Premrudee; Heale, Frances L.; Carmalt, Claire J.; Parkin, Ivan P.
Abstract : Robust superhydrophobic surfaces were fabricated via aerosol-assisted CVD of epoxy resins and PDMS polymer films. The as-obtained surfaces showed thermo-triggered healing of the superhydrophobicity by recovery of roughness structures. Abstract : Artificial self-healing superhydrophobic surfaces have become a new research hotspot because of their recoverable non-wetting performance and practical perspective. In this paper, a superhydrophobic surface was fabricated by aerosol-assisted layer-by-layer chemical vapor deposition (AA-LbL-CVD) of epoxy resins and PDMS polymer films. The obtained samples still showed superhydrophobicity even after long-term exposure to different pH solutions and UV light irradiation as well as great mechanical stability against sandpaper abrasion and double-sided tape peeling. Importantly, due to the shape memory effect of the polymer films, the as-prepared samples could recover the previously crushed micro–nano structures upon heat treatment to make the surface superhydrophobic, showing thermo-triggered healing of superhydrophobicity.